2012
DOI: 10.1029/2012gc004268
|View full text |Cite
|
Sign up to set email alerts
|

Major element variations in Hawaiian shield lavas: Source features and perspectives from global ocean island basalt (OIB) systematics

Abstract: [1] Among volcanic hot spots globally, Hawaii has the highest magma flux, yet there is significant controversy surrounding the composition of the mantle sourcing Hawaiian lavas. In order to place constraints on the source lithologies of Hawaiian lavas, we explore relationships between major elements and radiogenic isotopes in tholeiitic, shield-building lavas. Olivine-fractionation corrected lava compositions reveal clear trends between radiogenic isotopes and major elements. Individual data points exhibit rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 157 publications
(301 reference statements)
0
58
1
Order By: Relevance
“…At the University of Wisconsin-Madison Rare Gas Geochronology Laboratory, 40 Ar/ 39 Ar incremental heating experiments were conducted on groundmass and mineral separates using a 25 W CO 2 laser and analyzed using a MAP 215-50 following the procedures in Jicha and Brown (2014). Isotope data was reduced using ArArCalc software version 2.5 (http :/ /earthRef .org /ArArCALC/).…”
Section: Methodsmentioning
confidence: 99%
“…At the University of Wisconsin-Madison Rare Gas Geochronology Laboratory, 40 Ar/ 39 Ar incremental heating experiments were conducted on groundmass and mineral separates using a 25 W CO 2 laser and analyzed using a MAP 215-50 following the procedures in Jicha and Brown (2014). Isotope data was reduced using ArArCalc software version 2.5 (http :/ /earthRef .org /ArArCALC/).…”
Section: Methodsmentioning
confidence: 99%
“…The origin of the SiO 2 -rich nature of Koolau lavas from Hawaii is argued to be the result of eclogite melting in the Hawaiian mantle plume (Hauri, 1996;Herzberg, 2011;Sobolev et al, 2005), where the eclogite is suggested to be a recycled oceanic crust that preserved low U/Pb ratios through the subduction zone and generated relatively low time-integrated 206 Pb/ 204 Pb (Jackson and Dasgupta, 2008;Jackson et al, 2012). Hauri (1996 showed that existing peridotite melting experiments at pressures N 2 GPa (i.e., pressures that are slightly lower than the pressure at the base of mature oceanic lithosphere beneath Pitcairn and Hawaii) cannot generate the major element compositions observed in Koolau lavas, and more recent compilations of experimental data support this observation (see discussion in Jackson et al (2012)). Hauri (1996) Hauri (1996 also showed that elevated FeO at a given SiO 2 in Koolau lavas is a result of eclogite melting.…”
Section: The Presence Of Subducted Oceanic Crust In the Em-1 Pitcairnmentioning
confidence: 97%
“…However, there is growing petrologic and geochemical evidence, especially at Hawaii, for the presence of eclogite in the magma source region (Hauri, 1996;Farnetani and Samuel, 2005;Sobolev et al, 2005Sobolev et al, , 2007Herzberg, 2011;Jackson et al, 2012;Pietruszka et al, 2013), thought to originate from subducted oceanic crust and to be entrained by upwelling flow in the lower mantle (e.g., Deschamps et al, 2011). Because eclogite is denser than peridotite throughout the upper mantle and most of the lower mantle (Hirose, 2002;Aoki and Takahashi, 2004), the ascent of plumes containing both peridotite and eclogite will be influenced by a competition between non-diffusive, negative chemical buoyancy and diffusive, positive thermal buoyancy (e.g., Davaille, 1999).…”
Section: E-mail Address: Ballmer@hawaiiedu (Md Ballmer)mentioning
confidence: 99%
“…Bianco et al (2011) which is a characteristic criterion used to distinguish Loa versus Kea compositions (Abouchami et al, 2005). Thus, the geochemical difference between Loa and Kea lavas may be related to an asymmetric rise of the hottest eclogite-bearing plume core through the upper mantle rather than to a bilateral asymmetry of the deep plume conduit with distinct materials on the two sides ( On a more detailed level, trends in major-element versus isotope-ratio space have been interpreted as evidence for the presence of a second mafic component in the source, in addition to the pyroxenitic and peridotitic components modeled (Jackson et al, 2012). Such a more complex source composition is supported by the distinct slopes of the different volcanoes' trends in 208 Pb/ 204 Pb versus 206 Pb/ 204 Pb (Weis et al, 2011).…”
Section: Thermochemical Plume Dynamics In the Upper Mantlementioning
confidence: 99%